2021
DOI: 10.1038/s41467-021-21738-8
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic control of myofiber size and muscle protein quality control by the ubiquitin ligase UBR4 during aging

Abstract: Sarcopenia is a degenerative condition that consists in age-induced atrophy and functional decline of skeletal muscle cells (myofibers). A common hypothesis is that inducing myofiber hypertrophy should also reinstate myofiber contractile function but such model has not been extensively tested. Here, we find that the levels of the ubiquitin ligase UBR4 increase in skeletal muscle with aging, and that UBR4 increases the proteolytic activity of the proteasome. Importantly, muscle-specific UBR4 loss rescues age-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 63 publications
3
51
0
Order By: Relevance
“…In Figure 5 , we present an example of changes in proteostasis that occur with aging in mouse skeletal muscles. Specifically, with aging there is an increase in poly-ubiquitinated proteins found in the insoluble fractions of skeletal muscles from 24-month-old mice as compared to muscle from young 6-month-old mice ( Hunt et al., 2021 ), consistent with other studies ( Sakuma et al., 2016 ; White et al., 2016 ).
Figure 5 Decline in protein quality control in skeletal muscles during aging Western blotting of detergent-soluble and insoluble proteins fractions from tibialis anterior and soleus muscles from wild-type mice at 6 months (young) and 24 months (old) of age.
…”
Section: Expected Outcomessupporting
confidence: 90%
See 3 more Smart Citations
“…In Figure 5 , we present an example of changes in proteostasis that occur with aging in mouse skeletal muscles. Specifically, with aging there is an increase in poly-ubiquitinated proteins found in the insoluble fractions of skeletal muscles from 24-month-old mice as compared to muscle from young 6-month-old mice ( Hunt et al., 2021 ), consistent with other studies ( Sakuma et al., 2016 ; White et al., 2016 ).
Figure 5 Decline in protein quality control in skeletal muscles during aging Western blotting of detergent-soluble and insoluble proteins fractions from tibialis anterior and soleus muscles from wild-type mice at 6 months (young) and 24 months (old) of age.
…”
Section: Expected Outcomessupporting
confidence: 90%
“…Proteostasis decline with aging and defects in protein quality control are the underlying cause of multiple age-related diseases ( Douglas and Dillin, 2010 ; Labbadia and Morimoto, 2015 ). We have recently found that proteostasis declines during skeletal muscle aging (sarcopenia) in mice ( Demontis et al., 2013 ; Hunt et al., 2021 ; Jiao and Demontis, 2017 ), and that protein quality control is compromised across tissues and organ systems in the fruit fly Drosophila during aging ( Demontis and Perrimon, 2010 ; Rai et al., 2021 ). Moreover, by using thermal stress as a proxy for age-induced challenge to proteostasis, we have investigated the role of genetic and chemical interventions on proteostasis of human brain organoids and HEK293 cells ( Rai et al., 2021 ).…”
Section: Before You Beginmentioning
confidence: 99%
See 2 more Smart Citations
“…Atrogenes whose expression is increased in atrophying muscles include ubiquitin, core components of the 26S proteosome, eIF4E inhibitor 4E-BP1 ( Eif4ebp1 ), transcription factors Atf4 , Foxo1 , and Foxo3 [ 194 , 195 ], the muscle specific E3 ubiquitin ligases MurF1 ( Trim63 ) and Atrogin-1/MAFbx ( Fbxo32 ) [ 196 , 197 ], and autophagosome components LC3 ( Map1lc3a ) and Gabarap [ 194 , 198 , 199 ]. Importantly, animal models indicate that both insufficient [ 200 , 201 , 202 , 203 ] and excessive [ 198 , 199 , 204 ] proteolysis, both proteasomal and autophagic, negatively impact the muscle mass and functionality, suggesting an inflection point between a level of proteolysis that supports muscle homeostasis and that which promotes muscle wasting.…”
Section: Muscle Proteolytic Processes and Negative Regulation Of Anabolic Processesmentioning
confidence: 99%